What do adolescents think about vaccines? Systematic review of qualitative studies. - Hana Mitchell; Rebecca Lim; Prubjot K Gill; Joban Dhanoa; Ève Dubé; Julie A Bettinger (Public Library of Science (PLoS), 2022)
Adolescence presents a key opportunity to build vaccine-related health literacy and promote vaccine confidence and uptake. Although adolescents are central to vaccination programs, their views around vaccines are frequently underrepresented in qualitative literature. We reviewed qualitative studies to systematically identify and summarize existing evidence on adolescents' own understanding of vaccines and experiences with vaccine decision-making, including self-consent when applicable. CINAHL; Embase; Ovid Medline; and Psych Info database searches were last updated on May 28, 2022. Data pertaining to general study characteristics, participant demographics, and qualitative content were extracted independently by two reviewers and analyzed using textual narrative synthesis. Out of 3559 individual records, 59 studies were included. The majority of the studies were conducted in high-income countries and 75% focused on human papilloma virus vaccines, with the remaining studies looking at COVID-19, meningococcal, hepatitis B and influenza vaccines or adolescent experiences with vaccines in general. Adolescent self-consent was explored in 7 studies. Perspectives from sexual and gender minorities were lacking across studies. Adolescents often had limited understanding of different vaccines and commonly perceived vaccine information to be directed towards their parents rather than themselves. Many adolescents felt school-based vaccine education and information available through healthcare providers were insufficient to make informed decisions about vaccines. While adolescents described obtaining vaccine information from traditional and online media, face-to-face interactions and opinions from trusted adults remained important. Adolescents generally relied on their parents for vaccine-decision making, even when self-consent was an option. A notable exception to this included marginalized adolescents who could not rely on parents for health-related advice. Qualitative literature about adolescent vaccines would be enriched by studies examining vaccines other than the HPV vaccine, studies examining adolescent vaccine programs in low and middle-income countries, and by deliberately eliciting vaccine experiences of adolescent with diverse sexual orientation and gender identities.